2012
DOI: 10.17221/10/2012-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whole buckwheat flour on physical, chemical, and sensory properties of flat bread, Lavaş

Abstract: Yıldız G., Bilgiçli N. (2012): Effects of whole buckwheat flour on physical, chemical, and sensory properties of flat bread, Lavaş. Czech J. Food.Sci., 30: 534-540.The whole buckwheat flour (WBF) was used in Turkish flat bread, lavaş, up to 30% level without gluten, and up to 40% level with gluten and sodium stearoyl-2-lactylate (SSL) additions. Some physical, chemical, and sensory properties of lavaş bread samples were determined. While ash, crude fiber, phytic acid (PA), Fe, K, Mg, and P contents of lavaş br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…Yufka has 1–2 mm thickness and 40–50 cm diameter with cream color surface (Tekeli ; Başman and Köksel ). Bazlama and yufka can be supplemented with different ingredients such as cereal, pseudo‐cereal and legume flours or brans (Başman and Köksel , ; Coşkuner and Karababa ; Levent and Bilgiçli ; Yıldız and Bilgiçli ). The effect of sorghum flour (Yousif et al .…”
Section: Introductionmentioning
confidence: 99%
“…Yufka has 1–2 mm thickness and 40–50 cm diameter with cream color surface (Tekeli ; Başman and Köksel ). Bazlama and yufka can be supplemented with different ingredients such as cereal, pseudo‐cereal and legume flours or brans (Başman and Köksel , ; Coşkuner and Karababa ; Levent and Bilgiçli ; Yıldız and Bilgiçli ). The effect of sorghum flour (Yousif et al .…”
Section: Introductionmentioning
confidence: 99%
“…Rutin (Quercetin-3-O-glucorhamnosid) possesses important therapeutic properties, including a positive impact on the elasticity of blood vessels, treatment of disorders of blood circulation and atherosclerosis, blood pressure reduction and stimulation of the body to use vitamin C (Yildzogle-Ari et al, 1991). Several studies have reported the use of buckwheat products, such as flour, flakes, groats and extrudate, as substitutes for wheat flour in bakery, confectionery and pastry manufacturing technology (Borkowska & Robaszewska, 2012;Gavrilova, 2008b;Vandakurova & Stabrovskaya, 2008;Bonafaccia & Kreft, 1994;Yıldız & Bilgiçli, 2012;Baljeet, Ritika, & Roshan, 2010;Wang & Campbell, 2004;Lin, Liu, Yu, Lin, & Mau, 2009). The raw material for buckwheat flakes and buckwheat flour is buckwheat grain.…”
Section: Introductionmentioning
confidence: 99%
“…For bread containing 13% roasted buckwheat flour (BRF) and the corresponding control (C-BRF), a positive association was found the with adhesiveness, salty taste, mastication, and buckwheat odor and taste sensory qualities, and a negative association was found with the bran taste and odor and sweet taste and odor sensory qualities. Yildiz and Bilgiçli (2012) found that whole buckwheat flour negatively affected the sensory scores of lavaş (Turkish flat bread) when substituted at 40%, but the overall acceptability values did not change significantly compared to those for the control sample.…”
Section: Appearancementioning
confidence: 94%